Banking research in the time of COVID-19 - Berger, Allen N.; Demirgüç-Kunt, Asli (Journal of Financial Stability, 2021)
Despite the devastating worldwide human and economic tolls of the COVID-19 crisis, it has created some positive economic and financial surprises and opportunities for research. This paper highlights two such favorable surprises - the shortest U.S. recession on record and the avoidance of any banking crisis - and a number of research opportunities. The paper ties the "economic surprise" of the short recession to the speed and size of U.S. stimulus programs during COVID-19 - faster and larger than for the Global Financial Crisis (GFC). We connect the "financial surprise" of the resilient banking sector to prudential policies put in place during and after the GFC that fortified U.S. banks prior to COVID-19. These twin "surprises" are also mutually reinforcing - if either the economy or banking system had failed, so would the other. The paper also reviews extant COVID-19 banking research and suggest paths for future research. It recommends that particular attention be paid to research outside of the U.S. - where fewer favorable "surprises" may be present - as the best way to advance knowledge in this area.